The similarity between parents and offspring in facial soft tissue: a frontal-view study - Chang Chen-hsin; Miyazono Hisanobu; Komiya Tomoyuki; Nakasima Akihiko (Sciendo, 1998)
Similarities between parents and their offspring in facial soft tissue features were investigated. Fifty boys and fifty girls aged 9-10 years, excluding those with congenital anomalies, were selected. Frontal photographs of the family (father, mother and offspring) were taken and twenty-nine landmarks located on each enlarged tracing made from a photograph. Each landmark was digitised into (x, y) co-ordinate values from which the area and linear ratio dimensions were calculated and statistically evaluated. Results indicated that: (1) The nose was the feature that was most significantly correlated between parents and offspring. (2) The similarities between parents and offspring were closer for the relative positions of other features to the eyes than for individual features of the face. In generał, the correlations between 'midparents' (the mean value of both parents) and offspring were higher than those between one parent and offspring. (3) The correlations between parents and offspring for size were higher than those for shape. (4) The similarities between mothers and offspring were closer than those between fathers and offspring. Furthermore: among four pairs of father/son, father/daughter, mother/son and mother/daughter, the mother/daughter pair had the highest correlation and the father/son pair had the lowest, which appears to be related to X-chromosome inheritance.